2017
DOI: 10.1136/bmjopen-2017-018718
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the science of health research capacity strengthening in low-income and middle-income countries: a scoping review of the published literature, 2000–2016

Abstract: ObjectivesSubstantial development assistance and research funding are invested in health research capacity strengthening (HRCS) interventions in low-income and middle-income countries, yet the effectiveness, impact and value for money of these investments are not well understood. A major constraint to evidence-informed HRCS intervention has been the disparate nature of the research effort to date. This review aims to map and critically analyse the existing HRCS effort to better understand the level, type, cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 41 publications
(29 reference statements)
2
70
0
Order By: Relevance
“…Possible contributors to this authorship pattern include the dominance of high-income partners in consortium leadership, and broader structural and contextual factors which contribute to this imbalance such as resource and expertise constraints. Of note is that the nascent nature of the management-specific evidence reflects a similar trend in the broader HRCS literature, except that there is a better representation of LMIC authors in the latter 34. These imbalances and the factors contributing to them need to be addressed, with a particular emphasis on correcting the under-representation of LMIC perspectives in the available evidence.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Possible contributors to this authorship pattern include the dominance of high-income partners in consortium leadership, and broader structural and contextual factors which contribute to this imbalance such as resource and expertise constraints. Of note is that the nascent nature of the management-specific evidence reflects a similar trend in the broader HRCS literature, except that there is a better representation of LMIC authors in the latter 34. These imbalances and the factors contributing to them need to be addressed, with a particular emphasis on correcting the under-representation of LMIC perspectives in the available evidence.…”
Section: Discussionmentioning
confidence: 95%
“…Across the available evidence base, terms used for collaborations such as partnership, network and consortium are used inconsistently and interchangeably, a point also noted by others 59 89. Similarly, the concept of ‘(health) research capacity strengthening’ has been inconsistently applied across the broader HRCS literature 34. Thus, it is not entirely clear how an HRCS consortium might differ from a traditional health research consortium or how a consortium might differ from a partnership or network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The goal is to develop human resources and institutional capacity for effective research targeted at key priorities; (ii) global health governance and strengthening national health research systems, a primary interest of the Council on Health Research for Development (COHRED); 19,20 (iii) new strategies and action networks for disease control, which have received the support of academic organizations, international partnerships, and the WHO. 21,22 Embedding research into health policy and practice has become the key objective of several GHI. 23 Based on the thematic analysis, the current study showed an increasing interest in implementation research, an area that aims at bringing new strategies and interventions to practice by understanding barriers and facilitators of program implementation.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…We fully agree with proposals to advance antibiotic stewardship research in those countries [4,24], as evidenced by the fact that most of our group members collaborate with research partners in LMICs. However, the health research capacity strengthening research field with a focus on implementation science is emerging, and currently evidence bases are not yet sufficiently advanced to effectively inform health research capacity strengthening research programme planning [30]. On the basis of our best knowledge and experiences, we recognized that implementation of ASPs varies greatly across types of healthcare systems, let alone LMICs, so inviting a limited number partners from LMICs was likely to unfairly prioritize specific research needs in their countries.…”
mentioning
confidence: 99%